Investigation of the barriers about insulin therapy in patients with type 2 diabetes - Soylar, P.; Kadioglu, B. U.; Kilic, K. (Wolters Kluwer Medknow Publications, 2020)
Aims: This study aimed to explore barriers regarding insulin initiation in patients with Type 2 diabetes and investigate the relationship of some demographic characters of patients. Materials and Methods: A cross-sectional study was conducted with 142 patients with Type 2 diabetes whose doctors had recommended insulin therapy and who had been unwilling to comply. The participants were patients at an endocrine outpatient clinic in Kovancilar State Hospital in the rural area in Elazig, from November 2016 to May 2017. Results: Half of the patients were illiterate, 60.6% of the participants were female, and the mean age was 57.33 +/- 10.56. The most commonly reported barrier was injection-related anxiety (63.4%). In total, 58.5% of the patients refused insulin therapy because they felt it indicated that their disease had worsened and that they had failed at diabetes management. Female patients were 6.9 times more likely to think injection-related anxiety that affecting their decision about insulin therapy than male patients. Elderly patients were 8.2 times more likely to think of their disease worsened than younger patient. Conclusions: Patients' beliefs related to insulin therapy were very much influenced by their gender, educational status, and age. Giving patient-centered education is a cost-effective way to decrease negative health behaviors.
Keywords: Insulin; insulin initiation; Type 2 diabetes mellitus